Financing Peace: Special Autonomy Fund as a Peace Dividend in Aceh, Indonesia - Sustikarini, Amalia (JAS (Journal of ASEAN Studies), 2019)
This paper discusses the peacebuilding process in Aceh Indonesia. Southeast Asia is one of the regions that has been plagued by severe ethno-nationalist strives due to its high level of diversity and the impact of colonialism. Among several cases of ethno-nationalist struggles in this region, the separatist insurgency in Aceh, Indonesia has been regarded as the protracted conflict that has been successfully resolved and created durable peace. The Helsinki Peace Agreement attempted to redress the economic grievances that were manifested in perceived inequality and the exploitation of Aceh’s natural resources through the arrangement of Special Autonomy Fund. This fund serves as a peace dividend that is expected to bring welfare and enhance economic development in Aceh. The paper examines the role of Special Autonomy Fund in accelerating economic development in Aceh in the past ten years by utilizing the concept of the peace dividend and the model of fiscal-sharing. While this fund has been successfully increasing Aceh economic growth compared to the conflict era, it has not been optimally utilized to reduce poverty and inequality. Due to the nature of peace in Aceh as an elite-based peace, the peace dividend has contributed to the patronage politics particularly among the former combatants.